ELISA-Based Seroprevalence and Risk Factors for Toxocara Canis and Dirofilaria Immitis in Dogs in Khyber Pakhtunkhwa, Pakistan - Said, Arsalan; Saqib, Muhammad Najmus; Aziz, Tariq; Sadeeq, Muhammad; Adrian Shah, Shahzada Khurram; Faisal, Shah; Khan, Fahad Nawaz (Biological and Clinical Sciences Research Journal, 2025)
Parasites are responsible for several important and widespread zoonotic diseases transmitted through companionship between animals and humans. Zoonotic parasitic infections impact human and animal health and food safety and have significant economic implications. Limited data on the seroprevalence of Toxocara canis and Dirofilaria immitis infections in household dogs in Khyber Pakhtunkhwa, Pakistan. Objective: To determine the seroprevalence of Toxocara canis and Dirofilaria immitis in household dogs using a serological technique and to assess the associated risk factors. Methods: This cross-sectional study included 405 dog blood samples collected from veterinary facilities and private pet clinics across Khyber Pakhtunkhwa. An ELISA test was used to detect anti-Toxocara and anti-Dirofilaria IgG antibodies. Data regarding gender, age, area (rural/urban), and deworming status were gathered from owners through questionnaires. Chi-square tests were used to determine associations between seroprevalence and potential risk factors, with a significance level set at p < 0.05. Results: The overall seroprevalence was 22.71% (92/405; 95% CI: 18.9%–27.0%) for Toxocara canis and 2.22% (9/405; 95% CI: 1.1%–4.1%) for Dirofilaria immitis. For Toxocara canis, area (rural vs. urban, p < 0.05) and deworming status (p < 0.05) were significantly associated with infection. Age and gender were not significantly associated with Toxocara canis infection (p > 0.05). None of the investigated risk factors showed a statistically significant association with Dirofilaria immitis seroprevalence (p > 0.05). Conclusion: The study highlights a substantial seroprevalence of Toxocara canis and a lower prevalence of Dirofilaria immitis among household dogs in Khyber Pakhtunkhwa. Risk factors such as living in rural areas and a lack of deworming were associated with higher Toxocara infection rates. Effective control requires a comprehensive "One Health" strategy collaboratively addressing animal and human health.